Retail futures : the good, the bad and the ugly of the digital transformation - Pantano, Eleonora (Emerald Publishing Limited, 2020)
The book includes new theory, original empirical evidence, and applied case studies synthesizing advances in innovation and technology for the retail sector. Chapters identify the challenges retailers face in response to new practices, suggesting how the sector can respond to technological developments, ethical considerations and privacy issues.- Resumé vydavatel
Includes index.
Keywords: maloobchod; inovace; retail trade; innovations; elektronické knihy; monografie; electronic books; monographs